STUDY ON SPECIES COMPOSITION OF JUVENILE TUNA CAUGHT BY PURSE SEINE FLEET LANDING IN TAMPERAN FISHING PORT, JAVA, INDONESIA - Raymon Rahmanov Zedta; Bram Setyadji (Research Center for Fisheries, 2020)
Juvenile yellowfin tuna (Thunnus albacares) and bigeye tuna (T. obesus) are very similar in morphological characteristics, hence it is difficult to distinguish between these two species, especially when they are landed in frozen or defect conditions. The presence of juvenile bigeye tuna in yellowfin catch was first noticed in the 1980s from pole and line fisheries in Maldives. We analyzed the monthly composition structure of juvenile tuna caught by purse seine fleet operating in the South Indian Ocean. Tamperan fishing port was chosen for benchmarking to other small-scale fisheries. The result is expected to be used as an index for increasing the accuracy of juvenile tuna proportion for national catch statistics. A total of 4760 juvenile tunas were examined during monitoring activities. The length ranged 19-65 cm FL with median 40 cm FL for juvenile yellowfin tuna and 44 cm for juvenile bigeye. The whole weight of juvenile tuna ranged from 5 to 7 kg. The length-weight conversion for both species are W = 0.0184*FL3.0086 (R2 = 0.95, n = 4144) for juvenile yellowfin tuna and W = 0.018*FL3.0047 (R2 = 0.93, n = 346) for juvenile bigeye tuna. It can be inferred from the study that in terms of catch proportion of juvenile tuna, it consists of ratio 10:1, whereas for every 10 kg of juvenile tuna contains approximately one kg of bigeye tuna. Besides, the length-weight equation for both species is interchangeable, which means either equation can be performed to convert length to weight for both juvenile yellowfin and bigeye tuna.